1990
DOI: 10.1007/bf01969034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histamine on gastric acid secretion “in vitro”: Interference with endogenous prostaglandins

Abstract: The interference between histamine and endogenous prostaglandins (PGs) was investigated in the isolated gastric fundus from immature rats by evaluating the effect of nonsteroidal antiinflammatory agents (NSAIDs) on the acid response to histamine and the effect of histamine on PGs production by the gastric mucosa. Indomethacin (10(-5) M) and diclofenac (10(-5) M) caused a dose-dependent enhancement of the response to histamine, dimaprit and DBcAMP, but did not affect bethanechol-, isoprenaline- and forskolin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Of note, certain NSAIDs, such as diclofenac and piroxicam, while inhibiting prostaglandin synthesis also inhibit isolated gastric gland acid secretion by interacting with H + /K + ‐ATPase activity 13 . We and others have observed that NSAIDs stimulate basal acid secretion in vivo 7,10,11,14 and potentiate secretagogue‐stimulated acid secretion in vitro and in vivo 6,8,9,15,16 . A rational approach to prevent ulcerogenesis is to suppress the production of gastric acid, either with histamine H 2 receptor antagonists or proton pump inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, certain NSAIDs, such as diclofenac and piroxicam, while inhibiting prostaglandin synthesis also inhibit isolated gastric gland acid secretion by interacting with H + /K + ‐ATPase activity 13 . We and others have observed that NSAIDs stimulate basal acid secretion in vivo 7,10,11,14 and potentiate secretagogue‐stimulated acid secretion in vitro and in vivo 6,8,9,15,16 . A rational approach to prevent ulcerogenesis is to suppress the production of gastric acid, either with histamine H 2 receptor antagonists or proton pump inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…13 We and others have observed that NSAIDs stimulate basal acid secretion in vivo 7,10,11,14 and potentiate secretagogue-stimulated acid secretion in vitro and in vivo. 6,8,9,15,16 A rational approach to prevent ulcerogenesis is to suppress the production of gastric acid, either with histamine H 2 receptor antagonists or proton pump inhibitors. The latter have been shown to prevent the relapse of endoscopic ulcers in patients receiving long-term therapy with NSAIDs or COX-2 inhibitors.…”
Section: Introductionmentioning
confidence: 99%